MENAKAR AKAR PENENTU KINERJA KARYAWAN (Sudi Pada Perusahaan Freight Forwarder-PT.Ridho Trans Jaya Semarang) - aprih santoso; Niko Putra Helambang (Sekolah TInggi Ilmu Administrasi dan Manajemen Kepelabuhan (STIAMAK) Barunawati Surabaya, 2022)
The purpose of the study was to investigate the effect of competence, work environment, communication and person organization fit on employee performance at the Freight Forwarder Company-PT. Ridho Trans Jaya Semarang. The data analysis technique used multiple linear regression analysis. The population as well as the sample of this research are all employees of PT. Ridho Trans Semarang, totaling 43 employees. Questionnaires were used to obtain research data. The results of testing the coefficient of total determination showed that 50.4% of the changes in the dependent variable could be explained by independent variables, while the remaining 49.6% was explained by other variables outside the study. The results showed that each variable, namely competence, work environment, communication and person organization fit partially had a significant influence on employee performance. The value of the coefficient of determination adjusted R square is obtained at 76.8% which indicates that 76.8 percent of employee performance variables can be explained by the variables of competence, work environment, communication and person organization fit.